FAKTOR FAKTOR YANG MEMENGARUHI KEIKUTSERTAAN PESERTA BPJS MELAKUKAN SENAM PROLANIS DI PUSKESMAS MARTIMBANG KOTA PEMATANGSIANTAR TAHUN 2017 - Selamat Ginting; Eva Marini Tampubolon; Saiful Batubara (Jurnal Inovasi Kesehatan Masyarakat, 2020)
The transition of disease in Indonesia is marked by increasing cases of non-communicable diseases that are hospitalized in several hospitals. Non-communicable diseases are often referred to as chronic diseases. Non-infectious diseases contribute to 60 percent of death globally. Prolanic is a program aimed at encouraging members of people with chronic diseases to achieve optimal quality of life. The purpose of this research is to explain the factors that influence the participation of Social Assurance Security Agency participants doing Prolanic gymnastics at Public Health Center of Martimbang Pematangsiantar City. Type of research is analytical with cross sectional study design at Public Health Center of Martimbang Pematangsiantar City. The population was all 361 BPJS participants with a sample of 80 people. There is influence of knowledge, motivation, attitude, distance to participant Social Assurance Security Agency doing Prolanic Gymnastics with p value 0,001. The most dominant factor influencing the participation of Social Assurance Security Agency prolanic gymnastics is the knowledge with the expected value B is 0.007. Social Assurance Security Agency Pematangsiantar city is expected to do socialization about prolanic gymnastics and further research. Keywords: Prolanic Gymnastics, Social Assurance Security Agency of Members